Ovule and megagametophyte development in selected species of apeibeae and grewieae (malvaceae-grewioideae) from south America and its systematic implications - Lattar, Elsa Clorinda (2016)
Fil: Lattar, Elsa Clorinda. Consejo Nacional de Investigaciones Científicas y Técnica. Instituto de Botánica del Nordeste; Argentina.